Volti di Rossana Rossanda. L’‘opera’ inattesa di una “vecchia comunista” - Rea, Elisabetta (Status Quaestionis, 2025)
More than four years after Rossana Rossanda’s death, a series of studies and editorial curations have helped restore her multifaceted yet cohesive intellectual profile. This contribution focuses on the two volumes (2023) that collect and present to readers Rossanda’s critical and journalistic writings: Aperte lettere, edited by Francesco de Cristofaro, and Volti di un secolo, edited by Franco Moretti. These writings, drawn from what can be considered the ‘second act’ of Rossanda’s intellectual life – her journalistic career, following her earlier political militancy –, stand as both a testimony to a ‘total work’ and a dizzying journey through the 20th century. They reflect its narratives, suspended between nostalgia and contradictions, its revolutions, as well as the complex configurations that the relationship between intellectuals and politics gave rise to. One might choose to engage with these writings as an anachronistic, ‘unexpected’ reader, appreciating the productive friction with the present.